SGI‐110 and entinostat therapy reduces lung tumor burden and reprograms the epigenome. Issue 9 (5th April 2014) - Tellez, Carmen S.; Grimes, Marcie J.; Picchi, Maria A.; Liu, Yushi; March, Thomas H.; Reed, Matthew D.; Oganesian, Aram; Taverna, Pietro; Belinsky, Steven A.
<x xml:space="preserve">Abstract</x> The DNA methyltransferase (DNMT) inhibitor vidaza (5‐Azacytidine) in combination with the histone deacetylase inhibitor entinostat has shown promise in treating lung cancer and this has been replicated in our orthotopic lung cancer model. However, the effectiveness of DNMT inhibitors against solid tumors is likely impacted by their limited stability and rapid inactivation by cytidine deaminase (CDA) in the liver. These studies were initiated to test the efficacy of SGI‐110, a dinucleotide containing decitabine that is resistant to deamination by CDA, as a single agent and in combination with entinostat. Evaluation of in vivo plasma concentrations and pharmacokinetic properties of SGI‐110 showed rapid conversion to decitabine and a plasma half‐life of 4 hr. SGI‐110 alone or in combination with entinostat reduced tumor burden of a K‐ras/p53 mutant lung adenocarcinoma cell line (Calu6) engrafted orthotopically in nude rats by 35% and 56%, respectively. SGI‐110 caused widespread demethylation of more than 300 gene promoters and microarray analysis revealed expression changes for 212 and 592 genes with SGI‐110 alone or in combination with entinostat. Epigenetic therapy also induced demethylation and expression of cancer testis antigen genes that could sensitize tumor cells to subsequent immunotherapy. In the orthotopically growing tumors, highly significant gene expression changes were seen in key cancer regulatory pathways including induction of p21 and the apoptotic gene BIK. Moreover, SGI‐110 in combination with entinostat caused widespread epigenetic reprogramming of EZH2‐target genes. These preclinical in vivo findings demonstrate the clinical potential of SGI‐110 for reducing lung tumor burden through reprogramming the epigenome.